1984
DOI: 10.1007/bf00436138
|View full text |Cite
|
Sign up to set email alerts
|

Classification of hip joint dysplasia by means of sonography

Abstract: Our report relates to our experimental investigations and clinical experience gained with the sonography of infant hips. On the basis of over 3,000 sonograms we were able to carry out a standardization of dysplasia forms from the sonographic point of view. It is possible to recognize disturbed hip maturation already after birth and to continuously control the further development. New sonographic findings and details permit to take up a more differentiated therapy as applied so far.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
131
0
14

Year Published

1991
1991
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(146 citation statements)
references
References 3 publications
1
131
0
14
Order By: Relevance
“…At the Department of Orthopaedics at the University of Zurich, between 1993 and 2004, 386 children were treated for DDH type IIc or worse, according to Graf [8], before 6 months of age. Out of this collective, 150 patients were randomly selected for analysis of their treatment data and their final examination.…”
Section: Methodsmentioning
confidence: 99%
“…At the Department of Orthopaedics at the University of Zurich, between 1993 and 2004, 386 children were treated for DDH type IIc or worse, according to Graf [8], before 6 months of age. Out of this collective, 150 patients were randomly selected for analysis of their treatment data and their final examination.…”
Section: Methodsmentioning
confidence: 99%
“…In all patients, the harness was applied within 3 days of diagnosis. The sonograms were classified by Graf's method in terms of the α and β angles [1]. All sonograms were evaluated by an experienced ultrasonographer.…”
Section: Methodsmentioning
confidence: 99%
“…Ultrasound is a powerful tool in infant hip examination as numerous studies have reported and is a major diagnostic tool utilized frequently for screening purposes [24,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Quality of the image was assessed according to the presence or absence of major topographic points-morphological picture analysis by the Graph [24][25][26].…”
Section: Panel Evaluationmentioning
confidence: 99%